Rapid authentication of European sea bass (Dicentrarchus labrax L.) according to production method, farming system, and geographical origin by near infrared spectroscopy coupled with chemometrics - Ghidini, Sergio; Varrà, Maria Olga; Dall'Asta, Chiara; Badiani, Anna; Ianieri, Adriana; Zanardi, Emanuela (Food chemistry, 2019)
•Chemometric analysis of near infrared spectra of sea bass was performed.•Untargeted authentication of sea bass from different origins was feasible.•Variables responsible for discrimination were identified.•Discriminant models were internally and externally validated. Chemometric analysis of near-infrared spectroscopy (NIRS) data was applied to investigate the possibility to rapidly authenticate European sea bass (Dicentrarchus labrax L.) according to production method (wild or farmed), rearing system (extensive, semi-intensive or intensive), and geographical origin (Western, Central or Eastern Mediterranean Sea). NIR spectra from 1100 to 2500 nm were subjected to an exploratory principal component analysis (PCA) followed by orthogonal partial last square-discriminant analysis (OPLS-DA) to develop classifiers able to distinguish samples according to the various conditions under study. Models provided a correct classification rate of 100% for both wild and farmed sea bass, and of 67%, 80%, 100% for extensively, semi-intensively, and intensively-reared subjects, respectively. As for geographical provenance, 100% of Eastern, 88% of Central and 85% of Western Mediterranean Sea samples were correctly discriminated. The successful results obtained confirmed suitability of chemometric analysis applied to NIRS data for fast authentication of European sea bass origin.